Corporate power over human rights: an analytical framework - Birchall, David (Cambridge University Press, 2020)
This paper presents an original framework designed to systemize understandings of corporate power over human rights. The framework disaggregates four sites of this power: corporations have direct power over individuals’ human rights, power over the materialities of human rights, power over institutions governing human rights, and power over knowledge around human rights. This disaggregation is derived primarily from the work of Barnett and Duvall, and focuses on effects of corporate activity, rather than the Weberian understanding of power as the ability to achieve desired outcomes. The framework captures a broad set of corporate acts based on their (potential) harm to human rights. It is argued that understanding business and human rights through the lens of power can help to advance a more comprehensive account of business impacts on human rights.